An efficient Terahertz rectifier on the graphene/SiC materials platform - Schlecht, Maria-Theresa; Malzer, Stefan; Preu, Sascha; Weber, Heiko B. (Scientific Reports, 2019)
We present an efficient Schottky-diode detection scheme for Terahertz (THz) radiation, implemented on the material system epitaxial graphene on silicon carbide (SiC). It employs SiC as semiconductor and graphene as metal, with an epitaxially defined interface. For first prototypes, we report on broadband operation up to 580 GHz, limited only by the RC circuitry, with a responsivity of 1.1 A/W. Remarkably, the voltage dependence of the THz responsivity displays no deviations from DC responsivity, which encourages using this transparent device for exploring the high frequency limits of Schottky rectification in the optical regime. The performance of the detector is demonstrated by resolving sharp spectroscopic features of ethanol and acetone in a THz transmission experiment.<br
Keywords: Terahertz; Halbleiter-Bauelement

Length-dependence of light-induced currents in graphene - Boolakee, Tobias; Heide, Christian; Wagner, Fabian; Ott, Christian; Schlecht, Maria-Theresa; Ristein, Jürgen; Weber, Heiko B.; Hommelhoff, Peter (Journal of Physics B-Atomic Molecular and Optical Physics, 2020)
We investigate the transport of optically injected currents in graphene, a (semi-) metal with exceptional optical and electronic properties. We have recently shown that ultrashort laser pulses with low temporal symmetry drive coupled intraband motion and interband (Landau-Zener) transitions resulting in residual ballistic currents in graphene. Here we show experimentally how this current scales as a function of the distance between the light-induced current injection region and the adjacent metal contact electrodes and propose an approach to model the results based on diffusive and field driven charge transport. We expect this study to contribute to ongoing discussions on the propagation of light-field-controlled currents, a requirement for future lightwave electronics, operating at petahertz clock rate

Light-field–driven electronics in the mid-infrared regime: Schottky rectification - Schlecht, Maria-Theresa; Knorr, Matthias; Schmid, Christoph; Malzer, Stefan; Huber, Rupert; Weber, Heiko B. (Science Advances, 2022)

Light-Field Driven Electronics in the Mid-Infrared Regime: Schottky Rectification - Schlecht, Maria-Theresa; Knorr, Matthias; Schmid, Christoph; Malzer, Stefan; Huber, Rupert; Weber, Heiko B. (Science Advances, 2022)